1997
DOI: 10.1038/bjc.1997.489
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity from intensive chemotherapy combined with radiotherapy in breast cancer

Abstract: Summary Cardiac function was evaluated in 86 breast cancer patients after standard chemotherapy, followed by ablative chemotherapy and chest irradiation. One patient died of subacute heart failure 3 months after ablative chemotherapy. At a minimum of 1 year's follow-up (range 1-11 years) left vertricular ejection fraction (LVEF) was marginally abnormal in 4 of 27 disease-free survivors. One exceptional patient who received two transplantations is alive, with serious heart failure occurring after the second abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
(15 reference statements)
2
10
0
Order By: Relevance
“…The alterations of the functional parameters caused by DOX are similar to those observed in bioptic fragments of humans [Levey et al, 1979;Ganz et al, 1996;Postma et al, 1996;de Graaf et al, 1997] and rats [Iliskovic et al, 1997]. These results are also similar to the observations of other workers [Mimnaugh et al, 1983;Luo et al, 1997;Morishima et al, 1998Morishima et al, , 1999.…”
Section: Discussionsupporting
confidence: 89%
“…The alterations of the functional parameters caused by DOX are similar to those observed in bioptic fragments of humans [Levey et al, 1979;Ganz et al, 1996;Postma et al, 1996;de Graaf et al, 1997] and rats [Iliskovic et al, 1997]. These results are also similar to the observations of other workers [Mimnaugh et al, 1983;Luo et al, 1997;Morishima et al, 1998Morishima et al, , 1999.…”
Section: Discussionsupporting
confidence: 89%
“…It has been associated with the use of anthracyclines or radiotherapy and when both treatment modalities have been combined, the risk of cardiac toxicity has been enhanced [1,7]. However, most studies included patients who received chemotherapy and radiotherapy and, for this reason, it is very difficult to define the role of anthracyclines in cardiac toxicity.…”
Section: Discussionmentioning
confidence: 95%
“…de Graaf et al 18 reported 86 patients with locally advanced or metastatic breast cancer treated with doxorubicin or epirubicin-based induction chemotherapy and cyclophosphamide or mitoxantrone-based ablative chemotherapy. All patients had normal cardiac function before starting treatment.…”
Section: Bone Marrow Transplantationmentioning
confidence: 99%